Perspectives of the rural communities of Impendle, Bulwer, and Kokstad in South Africa using ethnomedicinal plants to cure flu and associated symptoms in the advent of COVID-19 - Zondi, Lungile Prudence; Ehaine, Stanley (International Journal of Indigenous Herbs and Drugs, 2022)
The contribution of ethnomedical research in the advent of infectious illness is not new. Ethnomedicinal plants have historically embodiment of wisdom from the ancestors and play a significant role in treating various human disorders. This study embodies qualitative research methods as well as the Social Constructivist Theory to understand how the rural communities (Impendle, Bulwer and Kokstad), located within the geographical landscape of South Africa use ethnomedicinal plants to cure flu and other associated symptoms in the advent of COVID-19. Through telephonic interviews, twenty (20) research participants were recruited using the snowballing-chain referral sampling technique. Research participants contributed by noting that rural communities/cultures have a rich knowledge of ethnomedicinal plants that they have used for decades to treat flu symptoms and even cure people suffering from flu. This paper strongly recognises that people’s voices in rural communities are important in understanding their illness or disease experience and how they ethnomedical respond to them. Data analysis revealed African activism towards the COVID-19 impact on rural communities. This paper thus recognises indigenous knowledge as ancestral learning, as the source of social, domestic wisdom as well as a guide on the use of ethnomedicinal plants/ethnomedicine. Ethnomedicinal plants remain the wealth of rural communities as they are able to demonstrate their agency and resilience when confronted by different illnesses. This is their contribution to the decolonial agenda which seeks to recognize the wealth of ethnomedical plants against the hegemonic pragmatism of biomedicine. This paper then proposes that discussed ethnomedicinal plants should be acknowledged in South Africa as well as in Southern Africa as their indigenous wealth and should be vetted as traditional remedies that people have used to cure flu and associated symptoms. This recognition will thus achieve decolonial thinking of African indigenous/ethnomedicinal plants.